Differences in the Effectiveness of Different Physical Therapy Modalities in the Treatment of Delayed-Onset Muscle Soreness: A Systematic Review and Bayesian Network Meta-Analysis - Chen J; Hu Q; Hu J; Liu S; Yin L (Journal of Pain Research)
Jing Chen,1– 3,* Qing Hu,1,2,* Jiajie Hu,1,2 Songtao Liu,1,2 Linyu Yin1,2 1Department of Rehabilitation Medicine, Affiliated Hospital (Clinical College) of Xiangnan University, Xiangnan University, Chenzhou, Hunan, People’s Republic of China; 2College of Medical Imaging Laboratory and Rehabilitation, Xiangnan University, Chenzhou, Hunan, People’s Republic of China; 3School of Acupuncture, Tuina and Rehabilitation, Hunan University of Chinese Medicine, Changsha, Hunan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Linyu Yin; Songtao Liu, Department of Rehabilitation Medicine, Affiliated Hospital (Clinical College) of Xiangnan University, No. 31, West Renmin Road, BeiHu District, Chenzhou, Hunan Province, 42300, People’s Republic of China, Tel +86 15173509798 ; +86 13875515541, Email 32666828@qq.com; 3370378@qq.comPurpose: Delayed-onset muscle soreness (DOMS) is a common clinical condition that frequently affects various populations. Physical therapy offers distinct advantages in managing this condition. However, many recently published studies have produced conflicting results and lack compelling evidence, complicating clinicians’ decision making. We employed a Bayesian meta-analysis to assess the efficacy and safety of physical therapy modalities (PTMs) for DOMS, aiming to provide robust, evidence-based medical insights for clinical application.Patients and Methods: We conducted a comprehensive search for randomized controlled trials (RCTs) evaluating PTMs for DOMS across databases, including CNKI, CSCD, CCD, CBM, PubMed, EMbase, Cochrane Library, and Web of Science, until October 22, 2024. The included studies were assessed for risk of bias using the Cochrane Risk of Bias Assessment tool, tailored for RCTs. A network meta-analysis was performed using R v.4.2.2.Results: At 24 hours post-intervention, photobiomodulation therapy(PBMT) demonstrated a significant advantage over placebo (− 3.91 [− 5.57, − 2.17],P< 0.05). The effects of other therapies were not significant (Cryotherapy: − 0.58 (− 1.20, 0.11), Cryotherapy combined with PBMT: 0.48 (− 1.09, 2.01), ES: − 0.98 (− 2.82, 0.89), Irradiated: − 0.10 (− 1.71, 1.53), STM: − 0.89 (− 2.63, 0.85), UT: − 0.61 (− 1.92, 0.84)).At 48 hours post-intervention, both PBMT (− 5.24 [− 6.95, − 3.20],P< 0.05) and sauna (− 3.29 [− 6.21,-0.33],P< 0.05) exhibited significant effects compared to placebo.The effects of other therapies were not statistically significant.; However, beyond 48 hours, there was no notable benefit from PTMs when compared with placebo, indicating that PTMs are more effective within the initial 48 hours, with PBMT yielding superior outcomes.Conclusion: The findings from this investigation indicate that PBMT and sauna treatment produce significant effects within the first 48 hours; however, beyond this period, the impact of photobiomodulation diminishes significantly. Overall, physical therapy modalities are the most effective within the 48-h window.Keywords: delayed-onset muscle soreness, physical therapy modalities, efficacy, systematic review, bayesian network meta-analysis